PELATIHAN KEPEMIMIPINAN BAGI PENGURUS OSIS SMU PARULIAN I MEDAN - Anda Yanny (Sean Institute, 2022)
Osis is an organization that is legalized all its activities by the school. Student Council activities that uphold the vision and mission of the school, of course, must have a responsible leader, and role model for its members. This community service activity aims to explore the potential of leadership talents that exist in students and student council administrators. As a Leader it is incumbent on him to advance his organization as a whole, including its members. The direction of member duties and supervision carried out to aggota certainly cannot be separated from the right way and can be understood by members. A leader is not an arrogant person, but a leader of character and is used as a role model by members